2019
DOI: 10.5902/1983465916992
|View full text |Cite
|
Sign up to set email alerts
|

Uma análise da relação entre valores pessoais e satisfação com o trabalho

Abstract: O objetivo deste estudo foi analisar a relação entre os valores pessoais e a satisfação com o trabalho. Para isso, foi feita uma regressão linear múltipla, cujas variáveis independentes foram valores pessoais e a variável dependente a satisfação com o trabalho. Os dados para este ensaio foram coletados a partir da base de dados European Social Survey com uma amostra válida de 820 indivíduos portugueses, quem participaram de um inquérito social o qual é aplicado anualmente em 20 países europeus aproximadamente.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
(42 reference statements)
1
1
0
Order By: Relevance
“…The complexity of this phenomenon is due to the fact that EE and job satisfaction are both affected by a wide range of different factors which differ not only according to the nature of work and job position but also according to personality traits, value hierarchies, and preferences of each individual. This diversity is confirmed by a number of studies [24], [25].…”
Section: Discussionsupporting
confidence: 63%
“…The complexity of this phenomenon is due to the fact that EE and job satisfaction are both affected by a wide range of different factors which differ not only according to the nature of work and job position but also according to personality traits, value hierarchies, and preferences of each individual. This diversity is confirmed by a number of studies [24], [25].…”
Section: Discussionsupporting
confidence: 63%
“…Several authors have already demonstrated that the values are related to individual aspects such as job satisfaction (Borell, Camfield, & Rodrigues, 2019), to the reduction of malaise (Matziari, Montgomery, Georganta, & Doulougeri, 2017), to behavioral aspects (Zawadzki et al, 2020) and even the meaning attributed to work (Bertosso, Ebert, Bonemberger, Centenaro, & Severo, 2019). In the organizational scope, investment in values contributes to sustainable development (Barrett, 2017;Polychroniou & Trivellas, 2018), and the image (Ariza-Montes, Arjona-Fuentes, Haan, & Law, 2018) because the organizations that choose to manage values they demonstrate an ethical attitude towards dealing with issues related to personal resources (Nielsen, Nielsen, Ogbonnaya, Kansala, Saari, & Isaksson, 2017).…”
Section: Introductionmentioning
confidence: 99%